2018
DOI: 10.1093/cid/ciy923
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Eastern Equine Encephalitis Virus From an Organ Donor to 3 Transplant Recipients

Abstract: Background In fall 2017, 3 solid organ transplant (SOT) recipients from a common donor developed encephalitis within 1 week of transplantation, prompting suspicion of transplant-transmitted infection. Eastern equine encephalitis virus (EEEV) infection was identified during testing of endomyocardial tissue from the heart recipient. Methods We reviewed medical records of the organ donor and transplant recipients and tested seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
(49 reference statements)
1
25
0
Order By: Relevance
“…In previous reports, EEEV IgM was detected as early as 1 day after the onset of symptoms, peaks 1-3 weeks after the onset of illness, and may remain positive for up to 3 months (Calisher et al, 1986a,b). The patient in this study had onset of encephalitis symptoms on DOI 7 (Pouch et al, 2018), making the observed decline in IgM between DOI 39 and DOI 48 consistent with a peak titer occurring in the first 3 weeks after symptom onset. Unfortunately, residual cerebrospinal fluid (CSF) samples were not available for testing from this EEEV patient to document the longitudinal course of CSF antibody production, although clinical testing revealed a positive CSF IgM antibody test on DOI 9 (Pouch et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…In previous reports, EEEV IgM was detected as early as 1 day after the onset of symptoms, peaks 1-3 weeks after the onset of illness, and may remain positive for up to 3 months (Calisher et al, 1986a,b). The patient in this study had onset of encephalitis symptoms on DOI 7 (Pouch et al, 2018), making the observed decline in IgM between DOI 39 and DOI 48 consistent with a peak titer occurring in the first 3 weeks after symptom onset. Unfortunately, residual cerebrospinal fluid (CSF) samples were not available for testing from this EEEV patient to document the longitudinal course of CSF antibody production, although clinical testing revealed a positive CSF IgM antibody test on DOI 9 (Pouch et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…EEEV was diagnosed on day 8 after transplantation based on positive EEEV IgM antibodies in cerebrospinal fluid. She had poor neurological recovery with repeat imaging demonstrating cerebral vasculitis and died 3 months post-transplantation (Pouch et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations